O horror no cinema de animação brasileiro: uma análise dos filmes do festival animaldiçoados - Nascimento, Genio (2017)
The objective of the present work was to draw a panorama through a survey and analysis of 84 Brazilian animations selected for the first seven editions (2010-2016) of the AnimalDooms - International Festival of Shadow Animation. For the analysis, the films themselves were considered, grouped in different tendencies: Classical, Escatológica, Folkloric, Comic and Experimental. To better understand the origin of these films, we also examine how teams are formed, the types of funding, and the techniques used. Our conclusions indicate that the characteristics of the current Brazilian horror animation accompany the main international trends of horror animation, which makes the Festival Animaldiçoados an event in which the Brazilian films find frank dialogue with their peers around the world.